2015
DOI: 10.1111/aas.12494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol or desflurane on post‐operative spirometry in elderly after knee surgery: a double‐blind randomised study

Abstract: Although there is a delay in awakening when using propofol, the effects of propofol on post-operative spirometry parameters are similar to those of DES when anaesthesia duration is approximately 3 h. Decreased respiratory parameters persisted up to 24 h after anaesthesia, irrespective of the choice of anaesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…The maintenance of MAP was better with sevoflurane compared with propofol. Although the difference may be of limited significance for healthy patients, the relative hypotension associated with propofol may be detrimental in elderly patients and patients with coronary artery disease (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of MAP was better with sevoflurane compared with propofol. Although the difference may be of limited significance for healthy patients, the relative hypotension associated with propofol may be detrimental in elderly patients and patients with coronary artery disease (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously compared the effect of propofol and inhalation anesthetics on lung functions in different surgical procedures, except for intracranial surgeries, Tiefenthaler et al [9] and Zoremba et al [10] reported that propofol impaired lung functions more than inhalation anesthetics. Alternatively, no significant difference was found in other studies [11,12] . Proper titration of the positive end expiratory pressure level according to lung compliance may reduce the side effects of anesthetic drugs on lung function.…”
Section: Introductionmentioning
confidence: 56%
“…Additionally, Tiefenthaler et al [9] have not disclosed their intraoperative ventilation strategy, which may have affected the study results. Kim et al [11] compared the effects of propofol and desflurane on the postoperative respiratory functions of elderly patients undergoing knee surgery. Similar to our results, they did not observe any differences in the postoperative spirometry values.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the reduction in FVC was greater after TIVA with propofolremifentanil than after sevoflurane-fentanyl-nitrous oxide anesthesia. However, TIVA had advantages such as less PONV, cough, and bronchoconstriction than inhalational anesthesia (33). We found reductions in postoperative FEV1/FVC in patients who had received propofol-based TIVA for their herniorrhaphy surgery.…”
Section: Discussionmentioning
confidence: 74%